Unpacking physical accessibility to primary education under the international covenant on economic, social and cultural rights: lessons for South Africa - Liphapang, Mpho (University of the Witwatersrand, Johannesburg, 2023)
Physical accessibility to primary education is a component of the feature of accessibility under the 4As framework of the UN Committee on Economic, Social and Cultural Rights. Up to the present time, the dimension of physical accessibility in the implementation of a primary education for children, has regrettably been the least engaged subject by human rights scholars, lawyers, and judges alike. This fact is reinforced in two main ways that are immediately apparent, namely (1) the scarcity of focused scholarship and judicial engagements on the subject, and (2) the minimal attention afforded to the content and meaning of physical accessibility when the subject is eventually engaged. These shortcomings have culminated in the emergence and broad acceptance of narrow theorisations of physical accessibility, through which the dimension is generally understood as a sole concern for schools to be situated at geographically convenient and accessible locations for the learners. In this research report, an examination of physical accessibility is undertaken with the aim to uncover its substantive content and meaning under the ICESCR, and to draw lessons on how it can contribute meaningfully to the achievement of a basic education in South Africa
A research report submitted in partial fulfillment of the requirements for the degree of Master of Laws by Coursework and Research Report School of law, University of the Witwatersrand, Johannesburg 2023
Keywords: Right to primary education; 4As; Physical accessibility; ICESCR; South Africa; UCTD; SDG-8: Decent work and economic growth